Elaboración de un manual de gestión ambiental basado en la norma ISO 14001:2004 para una empresa hormigonera - Pavón B, Christian (2010)
The current thesis talks about the elaboration of a Manual for the implementation of an Environmental Management System (EMS) based on the international norm ISO 14001, which was born from the necessity of the company DERNMIGON – Derivados de Hormigon S.A. of a environmentally responsible production, so there is a process in order to implement in the industry the necessary procedures for in the future, if the company believes that is convenient, to reach the ISO 14001 certification. For this, we drafted an environmental policy and procedures and environmental management programs to be followed in this type of industry, for its further development and implementation. This work presents the development of each step that need to be followed to develop a manual that allows the company to control all the activities, through established procedures, to minimize the impacts that they have on the environment, supporting environmental protection and prevention of pollution in balance with the needs of the company and its surroundings.